2016
DOI: 10.1002/ejoc.201600952
|View full text |Cite
|
Sign up to set email alerts
|

Six‐Membered Cyclic Nitroso Acetals: Synthesis and Studies of the Nitrogen Inversion Process of N‐Silyloxy‐3,6‐dihydro‐2H‐1,2‐oxazines

Abstract: Silyl nitronates undergo rhodium‐catalyzed formal [3+3]‐cycloaddition with enol diazoacetates to form N‐silyloxy‐3,6‐dihydro‐2H‐1,2‐oxazines. The scope of the reaction and the extent of the major side process were evaluated. A mechanistic scheme was proposed. The nitrogen inversion barrier in the obtained nitroso acetals was estimated based on both quantum calculations and kinetic measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…Alkyl (Me, 3b ; Et, 3c ), benzyl ( 3d ), p -nitrobenzyl ( 3e ), and phenyl ( 3f ) esters gave corresponding products in good yields. However, better results were achieved for electron-accepting 2,2,2-trichloroethyl ( 3a ) and p -nitrobenzyl ( 3e ) moieties, which is in line with the previously reported advantages of these substituents in C–H functionalization and cyclopropanation [ 53 , 54 , 55 , 56 ]. Poor yields and/or conversions were observed for vinyl diazoacetates with bulky tert -butyl ( 2g ) or BHT (2,6-di- tert -butyl-4-methylphenyl, 2h ) ester groups [ 57 ].…”
Section: Resultssupporting
confidence: 87%
“…Alkyl (Me, 3b ; Et, 3c ), benzyl ( 3d ), p -nitrobenzyl ( 3e ), and phenyl ( 3f ) esters gave corresponding products in good yields. However, better results were achieved for electron-accepting 2,2,2-trichloroethyl ( 3a ) and p -nitrobenzyl ( 3e ) moieties, which is in line with the previously reported advantages of these substituents in C–H functionalization and cyclopropanation [ 53 , 54 , 55 , 56 ]. Poor yields and/or conversions were observed for vinyl diazoacetates with bulky tert -butyl ( 2g ) or BHT (2,6-di- tert -butyl-4-methylphenyl, 2h ) ester groups [ 57 ].…”
Section: Resultssupporting
confidence: 87%
“…Since then, many studies have been reported on enantioselective transformations with 3‐siloxy‐2‐diazobutenoates, in which the initial reaction occurs at the vinylogous position of the carbene . Some notable examples include [3+2] cycloadditions with vinyl ethers and enamides, [3+3] cycloadditions with nitrones and other ylides and [4+3] cycloadditions with dienes . We have proposed the type of products formed from vinylogous reactions is dependent on whether the vinylcarbene reacts through the s‐ cis ( 1 ) or the s‐ trans ( 2 ) configuration (Scheme ) .…”
Section: Methodsmentioning
confidence: 99%
“…Metallo‐enolcarbenes generated catalytically from stable enoldiazo compounds exhibit electrophilic character at the vinylogous carbon and nucleophilic character at the metal carbene carbon, making them metallo‐1,3‐dipole equivalents . These versatile intermediates have emerged as a synthetically useful class of three‐carbon adducts when paired with a broad spectrum of dipoles and nucleophilic unsaturated compounds to construct cyclic molecules through [3+3]‐cycloaddition, or by [3+2]‐cycloaddition . Our intent was now to use these versatile intermediates for [3+1]‐cycloaddition reactions by addition/elimination with stable ylides whose nucleophilic reactivity would allow bond formation at the electrophilic vinylogous position of metallo‐enolcarbenes that, with displacement of a leaving group from the intermediate adduct, would form the desired [3+1]‐cycloaddition product.…”
Section: Methodsmentioning
confidence: 99%